(untitled) (Práxis Educativa, 2025)
This paper explores the structure, strategies, and ethical implications of contract cheating platforms in Spain, focusing on their advertising practices and digital infrastructures. Drawing on a mixed-methods analysis of 40 active websites and 643 associated advertisements, the study examines how these services present themselves as legitimate academic support. The findings reveal sophisticated marketing tactics, legal ambiguity, and a growing normalization of academic outsourcing. Platforms employ persuasive discourses of personalization, confidentiality, and success guarantees, often exploiting students’ academic stress. Most services offer comprehensive writing, editing, and tutoring packages, mimicking institutional language while evading direct reference to misconduct. The analysis highlights the commodification of higher education and the need for regulatory and educational responses. This work contributes novel empirical data to the under-researched Spanish context and informs global academic integrity debates. Keywords: Academic integrity. Contract cheating. Digital advertising. Higher Education. Academic outsourcing.